Use of prasugrel vs clopidogrel and outcomes in patients with and without diabetes mellitus presenting with acute coronary syndrome undergoing percutaneous coronary intervention. (15th January 2019) - Faggioni, Michela; Baber, Usman; Chandrasekhar, Jaya; Sartori, Samantha; Claessen, Bimmer E.; Rao, Sunil V.; Vogel, Birgit; Effron, Mark B.; Poddar, Kanhaiya; Farhan, Serdar; Kini, Annapoorna; Weintraub, William; et al.
Abstract: Background: Clinical trial data studies suggest superiority of prasugrel over clopidogrel in patients with diabetes. However, the use, safety and efficacy profile of prasugrel in unselected diabetic patients presenting with acute coronary syndromes (ACS) remain unclear. Methods: PROMETHEUS was a prospective multicenter observational study of 19, 919 ACS PCI patients enrolled between 2010 and 2013. The primary endpoint was 90-day major adverse cardiovascular events (MACE), comprising all-cause death, myocardial infarction, stroke or unplanned revascularization. The safety endpoint was bleeding requiring hospitalization. Results: We identified 7580 (38%) subjects with and 12, 329 (62%) without diabetes. Diabetic patients were older and had significantly higher rates of cardiovascular risk factors. However, they were less likely to receive prasugrel (18.2% vs. 21.7%). Use of prasugrel did not increase with the severity of clinical presentation in diabetics, whereas, among non-diabetics, prescription of prasugrel was higher in NSTEMI and STEMI compared to unstable angina. The 90-day and 1-year adjusted risk of MACE was greater in diabetics (at 1 year: 22.7% vs. 16.5%; HR 1.22 [1.14–1.33], p  < 0.001). At 1 year, the risk of bleeding was also higher in diabetics (4.9% vs. 4.1%, HR 1.19 [1.01–1.39], p  = 0.035). After multivariable adjustment, use of prasugrel was associated with a lower risk of death in diabetic patients both at 90 days and 1 year. Conclusions: Use of prasugrel in diabetic patients with PCI-treated ACS was lower than in non-diabetics despite their high-risk profile and the severity of their clinical presentation. In diabetics, prasugrel was associated with a lower adjusted risk of 90-day death compared with clopidogrel. Highlights: Use of prasugrel after PCI was lower in diabetic patients compared to non-diabetics. Prasugrel was chosen for younger patients, with lower rates of cardiovascular risk factors. In diabetics, prasugrel was associated with a lower risk of 90-day and 1-year death.